1996
DOI: 10.1159/000119261
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Anxiety Syndromes in a Normal Population

Abstract: The mortality of anxiety syndromes between 1972 and 1992 was investigated in a prospective study of a normal population, the 1947 Lundby cohort. 121 persons with anxiety according to the Lundby definition (Anx), and 74 persons with panic disorder with/without agoraphobia (PD-Ag) according to the DSM-III-R, all of them developing their first episode between 1947 and 1972, were analyzed with regard to general mortality and special cause of death. Sex-and age-specific mortality rates for these groups were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 15 publications
0
20
1
Order By: Relevance
“…The literature on anxiety and mortality is relatively sparse compared to that on depression. Previous studies have reported conflicting findings concerning the association between anxiety levels and mortality, which was reported as positive [12], absent [13,14], and negative [15]. Furthermore, we found lower mortality in participants with comorbid anxiety and depression compared to those with depression alone.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The literature on anxiety and mortality is relatively sparse compared to that on depression. Previous studies have reported conflicting findings concerning the association between anxiety levels and mortality, which was reported as positive [12], absent [13,14], and negative [15]. Furthermore, we found lower mortality in participants with comorbid anxiety and depression compared to those with depression alone.…”
Section: Discussioncontrasting
confidence: 75%
“…Scant studies have Seyed Hamzeh Hosseini et al, Anxiety and depression as predictors of MI mortality reported longer-term mortality data in MI patients; whereas one has found an association between an in-hospital depression and mortality 5 years later [10], the other has observed no association at 3-year follow-up [11]. Although symptoms of depression and anxiety overlap, little is known about how anxiety affects mortality, with reports of both positive and negative effects [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety in these patients has been found to be associated with high physical dependency and problems in the patient/carer relationship (Orrell & Bebbington, 1996). It negatively affects physical health leading to increased mortality rates (Grasbeck, Rorsman, Hagnell, & Isberg, 1996). A recent study (Schultz et al, 2004) found anxiety to be significantly associated with reduced functional status in performing activities of daily living, over and above the effects of cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, there is also the question of improving the wellbeing of the elderly person by adequate treatment, either pharmacological or with psychotherapy. An increased mortality in younger age groups, particularly in men, with anxiety disorders has also been reported (GraÈ sbeck et al, 1996). Data on this issue are lacking in the elderly.…”
mentioning
confidence: 99%